2013
DOI: 10.1038/ijo.2013.175
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte telomere length associates negatively with adipocyte size, whereas adipose tissue telomere length associates negatively with the extent of fibrosis in severely obese women

Abstract: Telomere length can be considered as a biological marker for cell proliferation and aging. Obesity is associated with adipocyte hypertrophy and proliferation as well as with shorter telomeres in adipose tissue. As adipose tissue is a mixture of different cell types and the cellular composition of adipose tissue changes with obesity, it is unclear what determines telomere length of whole adipose tissue. We aimed to investigate telomere length in whole adipose tissue and isolated adipocytes in relation to adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The relative length of telomeres was estimated by quantitative PCR as previously reported [40, 41]. Briefly, genomic DNA was extracted with Qiagen DNeasy Blood & Tissue Kit (Qiagen, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative length of telomeres was estimated by quantitative PCR as previously reported [40, 41]. Briefly, genomic DNA was extracted with Qiagen DNeasy Blood & Tissue Kit (Qiagen, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The telomere length was estimated by the relative ratio between the copies of telomere and the copies of β -globin (T/S). T/S value is calculated by 2 −ΔΔCt [40, 41]. …”
Section: Methodsmentioning
confidence: 99%
“…We observed only a few crown-like structures in obese and more specifically in SC adipose tissue 116 . No correlation was found between the number of crown-like structures and adipocyte hypertrophy in humans 65,74,76,117 .…”
Section: Inflammationmentioning
confidence: 97%
“…Bouazzaoui et al [25] reported that there was no correlation between the telomere length of obese human visceral adipose tissue and visceral adipocyte size. Lakowa et al [8] indicated that, in humans, there is no difference in telomere length between mature subcutaneous and mature visceral adipocytes.…”
Section: Discussionmentioning
confidence: 98%